COMMUNITY EMPOWERMENT THROUGH THE UTILIZATION OF MSMES IN THE TAMAN GHANJARAN AND SUMBER GEMPONG TOURISM VILLAGES, KETAPANRAME, TRAWAS, MOJOKERTO - Nikta, Segi Harimbia; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze community empowerment through the utilization of MSMEs in the Taman Ghanjaran and Sumber Gempong Ketapanrame Trawas Mojokerto Tourism Villages based on Mardi Yatmo Hutomo's community empowerment theory indicators. The main focus of the study is to identify the role of capital, infrastructure development, mentoring, institutional strengthening, and strengthening business partnerships in improving economic welfare and village tourism attractiveness. Method: The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. Research informants include BUMDes managers, MSME actors, community leaders, and village officials. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing/verification. Results: The results of the study indicate that the five indicators of community empowerment have been implemented well and are mutually supportive. Access to capital is obtained through a combination of village funds, savings and loans, and banking partnerships. The development of tourism and MSME supporting facilities and infrastructure is carried out in stages and according to needs. The mentoring program is carried out through business management and digital marketing training. Institutional strengthening is evident in the effective internal coordination of Village-Owned Enterprises (BUMDes), while business partnerships develop through collaboration with the government, the private sector, and local communities. Novelty: This research provides a new contribution by comprehensively integrating Mardi Yatmo Hutomo's community empowerment indicators in the context of MSME-based tourism villages. This approach demonstrates that the success of tourism village development relies not only on natural potential but also on structured, participatory, and sustainable empowerment strategies.